Digital Connections: Student Experiences in Online Language Exchanges - Bates, Daniel K.; Martinsen, Rob A.; Thompson, Gregory L. (IALLT Journal of Language Learning Technologies, 2018)
Exciting advances in technology have provided foreign language teachers with opportunities to connect students to native speakers of target languages. Much of the research in this area focuses on changes in proficiency or cultural sensitivity. Although valuable, the research is lacking in understanding students’ experiences online, including positive and negative feelings, challenges, as well as students’ overall opinions of the exchanges’ usefulness for learning. The present study used a mixed methods approach to examine the experiences of third-semester university students participating in online language exchanges with native speakers. A third-semester Spanish class at a large university consisting of 18 students was selected as a sample. Students were required to speak online with native Spanish speakers in the target language for 20 minutes each week. Students completed weekly surveys and a final survey, and three students were selected for semi-structured interviews. The data reveal common struggles that students face during online exchanges, methods students use for coping with these difficulties, areas of perceived growth, and social factors that affect students’ experiences. The article concludes with recommendations for what foreign language educators can do to support students in similar online exchanges.